KAJIAN Psidium guajava linn DAN Moringa oleivera lamk TERHADAP PERILAKU MENCIT YANG DIINDUKSI DIABETES MELLITUS TIPE 2 - Luthfi Hidayat Maulana; Resa Frafela Rosmi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Diabetes mellitus is a health problem with a high prevalence rate in Indonesia. One of the causes of the high prevalence and worsening of the prognosis of DM is the consumption of inappropriate foods (especially high-calorie foods). Psidium guajava Linn (guava) and Moringa oleivera Lamk (moringa) plants for Indonesian people are generally not a concern. Guava and Moringa have benefits used for antimicrobial and lowering blood glucose. The purpose of this study was to determine the effect of Psidium guajava Linn and Moringa oleivera Lamk on the behavior of mice induced by type 2 diabetes and to find an alternative treatment for diabetes mellitus that is cheap and safe. The research method uses an experimental laboratory with cross sectional design. Experimental animals (mice) type 2 DM induced nicotinamide injection 230 mg / kg BW and streptozotosin 65 mg / kg body weight. A total of 30 male Balb-C strain mice aged 2 months were divided into 6 groups: healthy controls, negative controls and treatment groups were given Psidium guajava L. and Moringa oleivera L. extracts. The results of fasting blood glucose levels in mice after being given extract therapy with consecutive concentrations of 5%, 10%, 20%, 40% respectively 107.94 mg / dL; 100.68 mg / dL; 80.98 mg / dL; 94.46 mg / dL and fasting blood glucose levels in the negative control group were 227.18 mg / dL. The treatment of Moringa oleivera L. and Psidium guajavana L. leaves extract affected the decrease in fasting blood glucose of DM type 2 mice; 2) The best decrease was shown by Moringa oleivera L. and Psidium guajavanaL. leaf extract with a concentration of 20% indicated by the Sig. 0,000 0.05